Neuroanesthesia Management in Cavernous Sinus Meningioma Craniotomy Patients - Rozi, Fakhriyadi; Prihatno, MM Rudi; Cahyono, Iwan Dwi (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2024)
AbstractThe most prevalent primary cavernous sinus (CS) lesion is cavernous sinus meningioma (CSM). Of all intracranial neoplasms, 1% are tumors in CS, and 41% are CSM. For contemporary neurosurgeons, orbital involvement in cavernous sinus meningiomas (CSMs) poses special difficulties. The condition is known as cavernous sinus meningioma (CSM) gradually impairs vision and may ultimately result in chiastic compression. Since January 2023, a male 55-year-old had been admitted to the hospital with cephalgia and mild diplopia in his right eye. Cavernous meningiomas were discovered using CT scans, and a craniotomy procedure was scheduled to remove the tumor. In order to facilitate intubation, the patient was given a premedication of sufentanyl for analgesia and was then given general anesthesia. Rocuronium was used to relax the muscles. Desflurane is an attractive option available to anesthesiologists to maintain general anaesthesia. This surgical procedure of removing intracranial tumours requires proper induction and monitoring of the patient's condition during surgery to prevent increased intracranial pressure. Intracranial elevation can cause systemic changes such as hypertension and changes in heart rhythm, as well as cerebral artery spasm, and lead to cerebral infarction and cerebral ischemia. An effective neuroanesthesia management program can help preserve hemodynamic stability and improve results during craniotomy surgery for the removal of meningiomas.